Identification and characterization of two novel α-glucosidase inhibitory peptides from almond (Armeniaca sibirica) oil manufacture residue. (December 2020) - Gu, Xin; Gao, Tao; Hou, Yakun; Li, Di; Fu, Le
Abstract: Almond consumption is associated with ameliorating type 2 diabetes mellitus (T2DM). The purpose of this study is to isolate peptides with high α-glucosidase inhibitory activity from almond ( Armeniaca sibirica ) oil manufactured residue hydrolysate by ultrafiltration, gel chromatography and reversed-phase high-performance liquid chromatography (RP-HPLC) and to characterize their structures. The results indicated that the nutritional values of Var, Met+Cys, Ile, and Leu were high in almond oil residue, and the first limiting amino acid was Lys. Two peptides recovered from hydrolysed products of Prote Ax and Protease M were Trp-His and Trp-Ser, respectively, which showed higher α-glucosidase inhibitory activity compared with other peptides. These two peptides were relatively stable under simulated digestion conditions. The α-glucosidase inhibitory activity IC50 of Trp-His was 17.03 ± 0.05 μmol/L for both before and after digestion, whereas the IC50 of Trp-Ser significantly increased after simulated digestion, from 24.71 ± 0.02 μmol/L to 44.63 ± 0.03 μmol/L. These results indicated the potential use of residue from almond oil processing for treating T2DM. Highlights: Protein from almond oil manufacture residue was evaluated. Peptide A and B were isolated from protein of almond oil manufacture residue. The structure of A and B were characterized. Peptide A and B showed excellent α-glucosidase inhibitory activity. The changes in structure and activity were investigated after simulated digestion.